2022
DOI: 10.3390/plants11212846
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Structural Features of Hydrocinnamic Acid Related to Its Allelopathic Activity against the Parasitic Weed Cuscuta campestris

Abstract: Cuscuta campestris is a parasitic weed species that inflicts worldwide noxious effects in many broadleaf crops due to its capacity to withdraw nutrients and water directly from the crop vascular system using haustorial connections. Cuscuta campestris control in the majority of crops affected is non-existent, and thus, research for the development of control methods is needed. Hydrocinnamic acid occurs naturally in the rhizosphere, playing regulatory roles in plant–plant and plant–microbe communities. The toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…The inhibitory activity of derivative compounds with halogenated substituents on the aromatic ring (namely, compounds 18 – 21 ) was increased when compared with trans -cinnamic acid ( 1 ). This finding agrees with a previous study where halogenated substituents increased the activity of the parent compound hydrocinnamic acid ( 2 ) against C. campestris growth [ 26 ] but disagrees with Nishikawa et al [ 28 ], who report similar or slightly less activity for halogenated analogs when compared with the cis -isomer of cinnamic acid. In our work, the growth inhibitory effect of halogenated derivatives was dependent on the type of halogenated substituent and its position.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The inhibitory activity of derivative compounds with halogenated substituents on the aromatic ring (namely, compounds 18 – 21 ) was increased when compared with trans -cinnamic acid ( 1 ). This finding agrees with a previous study where halogenated substituents increased the activity of the parent compound hydrocinnamic acid ( 2 ) against C. campestris growth [ 26 ] but disagrees with Nishikawa et al [ 28 ], who report similar or slightly less activity for halogenated analogs when compared with the cis -isomer of cinnamic acid. In our work, the growth inhibitory effect of halogenated derivatives was dependent on the type of halogenated substituent and its position.…”
Section: Resultssupporting
confidence: 84%
“…In our work, the growth inhibitory effect of halogenated derivatives was dependent on the type of halogenated substituent and its position. On one side, when considering the substitution in the para position, the most phytotoxic compound was that containing the largest and more electronegative halogen Br ( 21 , Figure 3 D) > Cl ( 20 ) > F ( 19 ), confirming the activity of equivalent halogenated substituents in hydrocinnamic acid reported by Moreno-Robles et al [ 26 ] and cis -cinnamic acid reported by Nishikawa et al [ 28 ]. In addition, when comparing the results of compounds containing the same halogen in different positions, the one with a Cl atom in the meta position (compound 18 , IC 50 = 461 µM) presented enhanced phytotoxicity when compared to the para -substituted isomer (compound 20 , IC 50 = 955 µM).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The methyl group substitution at C-4 of the benzene ring increased the activity, but the hydroxyl group at C2–4 decreased the activity of phenylpropanoid dihydrocinnamic acid against parasitic weed ( Cuscuta campestris Yunk.) [ 29 ]. Among the six coumarin analogs synthesized from eugenol, 8-methoxy-2-oxo-6-(prop-2-en-1-yl)-2H-chromene-3-carboxylic acid presented the highest phytotoxic activity against lettuce seedlings ( L. sativa L.).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dibenzopyronederivatives alternariol (3) and alternariol 4-methyl ether (4), the higher necrotic effects showed by compound 3 could be explained by the hydroxyl group placed in the position where compound 4 presents a methoxy group, hinting that polar groups could have a positive effect on the necrosis-inducing activity, due to the capacity of forming H-bonds [50]. For both compounds, found herein as necrotic-causing toxins on lemon fruits, but inactive on pear fruits (host and non-host species), other previous studies reported activities of interest.…”
Section: Compoundmentioning
confidence: 99%